A Wearable Wireless Energy Link for Thin-Film Batteries Charging. (24th March 2016) - Monti, Giuseppina; Corchia, Laura; De Benedetto, Egidio; Tarricone, Luciano
Abstract : A wireless charger for low capacity thin-film batteries is presented. The proposed device consists of a nonradiative wireless resonant energy link and a power management unit. Experimental data referring to a prototype operating in the ISM band centered at 434 MHz are presented and discussed. In more detail, in order to facilitate the integration into wearable accessories (such as handbags or suitcases), the prototype of the wireless energy link was implemented by exploiting a magnetic coupling between two planar resonators fabricated by using a conductive fabric on a layer of leather. From experimental data, it is demonstrated that, at 434 MHz, the RF-to-RF power transfer efficiency of the link is approximately 69.3%. As for the performance of the system as a whole, when an RF power of 7.5 dBm is provided at the input port, a total efficiency of about 29.7% is obtained. Finally, experiments performed for calculating the charging time for a low capacity thin-film battery demonstrated that, for RF input power higher than 6 dBm, the time necessary for recharging the battery is lower than 50 minutes.